EU renewable electricity law and policy : from national targets to a common market - Rusche, Tim Maxian (Cambridge : Cambridge University Press, 2015)
There are two basic policy tools for promoting renewable electricity: price regulation (feed-in tariffs) and quantity regulation (green certificates). In economic theory, they are equally efficient. Contrary to conventional thinking, the author demonstrates that under real-world conditions, price regulation is more efficient. EU law obliges Member States to put support schemes in place, but leaves their design to national authorities. They need, however, to comply with EU state aid and internal market rules, and their financing may not result in import duties and discriminatory taxation. This book provides a detailed analysis of the decisions practice adopted by the Commission and the case law of the Union Courts. As support schemes mature, has time not come for putting an end to regulatory competition? With huge efficiency gains to be expected, the author expertly examines the political obstacles and sets out three different pathways to achieve EU-wide harmonization.
Regulation of renewable electricity in the internal electricity market : (still) a preserve of member states -- The regulatory options from an economic point of view: superiority of prices over quantities under real-world conditions -- The times they are a-changin'? the evolution of support schemes in member states over time -- Union law on state aid : down for the count, but not knocked out by PreussenElektra -- Union law on free movement of goods : the protection of the environment justifies (nearly) everything, except for "buy European" clauses for equipment -- Prohibition of internal customs duties and discriminatory taxation : the sometimes forgotten straightjacket -- 2013 to 2015 : years of upheaval? -- Regulatory options for the creation of a common market -- Regulatory cross-fertilization across the Atlantic.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Electric power-plants -- Law and legislation -- European Union countries; Renewable energy sources -- Law and legislation -- European Union countries